Elaboración e implementación de un manual de seguridad industrial y salud ocupacional para prevenir los riesgos laborales del personal que trabaja en la empresa omega maquinarias y equipos ubicada en la ciudad de Riobamba, provincia de Chimborazo - Erazo Baño, Sonia Jaqueline (2017)
The research aims to develop and implement a manual of industrial safety and occupational health to prevent occupational hazards in the personnel working in the company OMEGA machinery and equipment located in the city of Riobamba, province of Chimborazo. Regarding the impact of work on the occupational safety and health process in the increase of incidents, accidents and occupational diseases; Added to the technical failures due to lack of training in the company and the non-application of the corresponding regulations makes that the company can incur fines by the control organisms. Through research instruments such as the survey and unstructured and non-participant observation, the necessary information was collected; for the application of the instrument was necessary the elaboration of a questionnaire the same that was applied to the administrative and production personnel of the company. Of the main results of the investigation it was determined that the lack of a manual of occupational safety and health caused incidents, accidents and as a result labor injuries, also did not have the tools and equipment sufficient to carry out the necessary activities, health services were shared and in the same did not exist any type of cleaning utensils; to finish, there was no type of signage that would allow workers to know about the dangers. The proposal is designed to reduce the number of accidents and incidents at work, and through prevention seeks to safeguard the physical and psychological integrity of the personnel of the company Omega Maquinarias y Equipos. The proposal consists of the design of the Safety and Health Manual, which establishes guidelines and safety standards. After the implementation, the survey was carried out again in order to determine the required results, noting that a reduction in work accidents from 83% to 17% was achieved in terms of training on hazards to those exposed at work, as well as training focused on the prevention of accidents or illnesses has been improved by 100%, providing employees with the resources necessary to carry out the tasks entrusted. The respective hypothesis was verified, which maintains that the elaboration and implementation of a Manual of Industrial Safety and Occupational Health will minimize labor accidents in the OMEGA Machinery and Equipment Company located in the city of Riobamba Province of Chimborazo.